Hour of the Red God - Crompton, Richard, 1973- (Sarah Crichton Books/Farrar, Straus and Giroux, 2013)
Detective Mollel, a former Maasai warrior in Nairobi, investigates the brutal murder of a prostitute and suspects the killing is part of a far more extensive plot associated with the turbulent elections of 2007.